2005
DOI: 10.1136/bjo.2004.060582
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal crossing of the optic fibres shown by evoked magnetic fields in patients with ocular albinism with a novel mutation in the OA1 gene

Abstract: Aim: To perform genealogical and clinical studies in Finnish families with X linked ocular albinism (OA1), including characterisation of the potential misrouting of optic fibres by evaluating visual evoked magnetic fields (VEFs), and to determine the mutation behind the disease. Methods: Three families with OA1 were clinically examined. VEFs were measured in two affected males and in one female carrier to characterise the cortical activation pattern after monocular visual stimulation. The neuronal sources of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The achiasma syndrome has also been observed in a patient with nystagmus (Korff et al 2003). Misrouting of the optic fibers in some patients with ocular albinism has been revealed by use of visually evoked magnetic fields (VEFs) (Ohde et al 2004;Lauronen et al 2005). Functional magnetic resonance imaging (fMRI) studies of some patients with oculocutaneous albinism revealed abnormalities in the optic nerve head (Kasmann-Kellner et al 2003;Morland et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The achiasma syndrome has also been observed in a patient with nystagmus (Korff et al 2003). Misrouting of the optic fibers in some patients with ocular albinism has been revealed by use of visually evoked magnetic fields (VEFs) (Ohde et al 2004;Lauronen et al 2005). Functional magnetic resonance imaging (fMRI) studies of some patients with oculocutaneous albinism revealed abnormalities in the optic nerve head (Kasmann-Kellner et al 2003;Morland et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…33 Findings in individuals with albinism using visual-evoked potential and magnetic resonance imaging studies are consistent with previous animal studies. 34,35 Children with ADHD alone may also have abnormal brain circuitry, especially in the prefrontal cortex, with secondary effects on behavior and visual-spatial working memory. 36 There are some limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A three-lead visual evoked potential (VEP) shows a characteristic finding of reversed polarity (interhemispheric potential difference) due to abnormal decussation of retino-striate fibers passing through the optic chiasm [104][105][106][107][108][109][110]. In patients with ocular albinism, 75-85% of nerve fibers decussate to the contralateral side in contrast to 55% in normal individuals.…”
Section: Affected Menmentioning
confidence: 96%